Study on the mechanism of acute liver injury protection in Rhubarb anthraquinone by metabolomics based on UPLC-Q-TOF-MS - Gong, Xiaohong; Zhang, Fang; Li, Yunxia; Peng, Cheng (Frontiers in Pharmacology, 2023)
As a traditional Chinese medicine, rhubarb has been used in a variety of liver diseases and it is widely used in clinic to prevent and treat acute liver injury. Anthraquinone, as the main medicinal component of rhubarb, can reverse the further development of liver fibrosis caused by acute liver injury. In this study, metabonomics was used to explore the mechanism of different doses of rhubarb anthraquinone on acute liver injury in rats. Rhubarb anthraquinone was administered intragastric to rats at doses of 3.9 mg/kg, 7.8 mg/kg and 15.6 mg/kg, respectively, for 7 days, and then 30% CCl4 was injected intraperitoneally at the dose of 1mL/kg to replicate the acute liver injury model. The biochemical indicators content of ALT, AST, ALP, gamma-GT, TG, TC, LDL, HDL in serum and GSH, Hyp, SOD, TNF-, IL-6 and IL-8 in liver tissue were tested respectively, and liver tissue was histopathologically analysis. At the same time, UPLC-Q-TOF-MS combined with non-targeted metabolomics was used to study the metabolites and metabolic pathways of rhubarb anthraquinone in treating acute liver injury. Compared with normal rats, the contents of ALT, AST, ALP, TG, TC, LDL, γ-GT in serum and Hyp, MDA, IL-6, IL-8, TNF-α in the liver tissue were significantly increased in model rats (P<0.05, P<0.01), and the content of HDL in the serum was significantly decreased (P<0.05），the activities of GSH and SOD in liver tissue were also significantly decreased (P<0.05). After administration of rhubarb anthraquinone, compared with the model group, with the increase of dosage, some biochemical indexes showed opposite changes, and gradually approached to normal rats. And the biosynthesis and metabolism of phenylalanine, tyrosine and tryptophan, the metabolism of amino sugars, nucleotide sugars and pyrimidines metabolism, and the biosynthesis of steroid hormone were identified based on the biomarker analysis. Based on the biochemical analysis and metabonomics analysis of rats with acute liver injury treated with different doses of rhubarb anthraquinone, combined with histopathological observation.